1995
DOI: 10.1016/0010-938x(94)00109-j
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the passivation and localized corrosion of α- and β-brass in borate buffer solutions containing sodium chloride—II. X-ray photoelectron and Auger electron spectroscopy data

Abstract: The composition of corrosion layers formed on a-, /3-and (a + &brass anodized in the passive region in borate-boric acid buffer and 0.5 M NaCl + borate-boric acid buffer (pH 9) was studied comparatively by X-ray photo-electron and Auger electron spectroscopy. Passivation of brass in both solutions involves the formation of a complex passive layer consisting of ZnO and CyO. In both solutions, the ZnO electroformation results in a dezincification so that a thin Cu rich layer is formed at the alloy/metal oxide in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 6 publications
1
29
0
Order By: Relevance
“…It can be seen that in the case of the CuZn system, these reduction peaks are somewhat shifted to lower potentials and are less distinct, however, it is clear that Q1 corresponds to the reduction of Cu(II), Q2 to the reduction of Cu(I) and Q3 to the reduction of Zn(II). These data are in agreement with those reported by Morales et al [19,20], who observed a potential shift in the reduction of Cu(II) and Cu(I) for various brasses.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…It can be seen that in the case of the CuZn system, these reduction peaks are somewhat shifted to lower potentials and are less distinct, however, it is clear that Q1 corresponds to the reduction of Cu(II), Q2 to the reduction of Cu(I) and Q3 to the reduction of Zn(II). These data are in agreement with those reported by Morales et al [19,20], who observed a potential shift in the reduction of Cu(II) and Cu(I) for various brasses.…”
Section: Resultssupporting
confidence: 93%
“…5, which were obtained following a 90-min immersion period, that the oxide layers existing under opencircuit conditions contain a relatively large amount of copper oxides. However, the outer layers will contain ZnO as shown by Morales et al [19,20] and the concentration of ZnO will be higher during the early stages of immersion. It is well known that ZnO is an n-type semiconductor [12 -15].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…As mentioned above, the XPS Zn2p 3/2 peak for metallic state is undistinguishable from that of Zn 2+ [30][31][32][33][34][35][36][37][38]. In such cases, ZnLMM Auger transitions induced by X-ray radiation (Fig.…”
Section: Resultsmentioning
confidence: 67%